Factors of development of modern forms of social and labor relations as a way of improving productivity in the aviation enterprises - K. S. Ermakov; A. V. Savyolova (Научный вестник МГТУ ГА)
The article is devoted to the factors of development of modern forms of social and labor relations as a way to increase productivity on airlines. We describe economic and social issues of a new form of labor relations - working from home. We review the brand new chapter of Labor Code of Russian Federation about working from home as a legal way to conclude telework agreement with the employee. This is a model of working from home for aviation enterprise based on typical performance of “Aeroflot - Russian airlines”.